GOODS AND SERVICES TAX (GST) FROM INDIAN ASPECTS: CHARACTERISTICS & CHALLENGES (CAHIERS MAGELLANES-NS, 2024)
The long-awaited Goods and Services Tax (GST) is India's biggest tax reform since independence. By replacing a number of different taxes with a single, unified tax, the GST is intended to streamline India's indirect tax system. The only indirect tax that directly links every sector of the Indian economy is the Goods and Services Tax (GST), which fosters the development of a single, unified market and accelerates national economic progress. France is the country that has introduced the GST followed by more than 160 other countries worldwide. In 1999, Atal Bihari Vajpayee introduced the concept of Goods and Services Tax (GST) in India. Asim Das Gupta, the finance minister of West Bengal at the time, led the formation of a committee. It was intended to go into effect on April 1st, 2010, under the direction of P Chidambaram, the UPA government's finance minister at the time. However, political squabbles and competing stakeholder interests prevented it from happening. The Lok Sabha approved the GST constitutional amendment bill in May 2016, and India's finance minister, Arun Jaitley, set a deadline of April 1, 2017, for the implementation of the tax. There is a lot of opposition to its implementation, though. This study focuses on the implementation issues that India has experienced and provides an outline of the Goods and Services Tax (GST) concept, advantages and features.